Speech teaching to the deaf : a practical handbook - Wright, John Dutton, 1866-1952 (New York : The Wright Oral School, 1931)
Educational Needs of the Deaf What the Mother of a Deaf Child Ought to Know Handbook of Practical Auricular Training The Little Deaf Child, A book for parents